Melioidosis in travelers: An analysis of Dutch melioidosis registry data 1985–2018. Issue 32 (November 2019) - Birnie, Emma; Savelkoel, Jelmer; Reubsaet, Frans; Roelofs, Joris J.T.H.; Soetekouw, Robin; Kolkman, Saskia; Cremers, Anne Lia; Grobusch, Martin P.; Notermans, Daan W.; Wiersinga, W. Joost; ,
Abstract: Background: Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, is an opportunistic infection across the tropics. Here, we provide a systematic overview of imported human cases in a non-endemic country over a 25-year period. Methods: All 55 Dutch microbiology laboratories were contacted in order to identify all B. pseudomallei positive cultures from 1990 to 2018. A response rate of 100% was achieved. Additionally, a systematic literature search was performed, medical-charts reviewed, and tissue/autopsy specimens were re-assessed. Results: Thirty-three travelers with melioidosis were identified: 70% male with a median-age of 54 years. Risk factors were present in most patients (n = 23, 70%), most notably diabetes (n = 8, 24%) and cystic fibrosis (n = 3, 9%). Countries of acquisition included Thailand, Brazil, Indonesia, Panama, and The Gambia. Disease manifestations included pneumonia, intra-abdominal abscesses, otitis externa, genitourinary, skin-, CNS-, and thyroid gland infections. Twelve (36%) patients developed sepsis and/or septic shock. Repeat episodes of active infection were observed in five (15%) and mortality in four (12%) patients. Post-mortem analysis showed extensive metastatic (micro)abscesses amongst other sites in the adrenal gland and bone marrow. Conclusions: The number of imported melioidosis is likely to increase, given rising numbers of (immunocompromised) travelers, and increased vigilance of the condition. This first systematic retrospective surveillance study in a non-endemic melioidosis country shows that imported cases can serve as sentinels to provide information about disease activity in areas visited and inform pre-travel advice and post-travel clinical management.